What does it mean to put new hepatitis C drugs on a list of essential medicines?. (22nd April 2016) - Urrutia, Julian; Porteny, Thalia; Daniels, Norman
Abstract : Expensive treatments for common conditions are unaffordable for most health system, even if they are cost effective. Julian Urrutia and colleagues examine how countries could respond to WHO making direct acting antivirals essential medicines